Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2009
DOI: 10.4049/jimmunol.0802911
|View full text |Cite
|
Sign up to set email alerts
|

Cutting Edge: IL-7 Regulates the Peripheral Pool of Adult RORγ+ Lymphoid Tissue Inducer Cells

Abstract: During fetal life, CD4+CD3− lymphoid tissue inducer (LTi) cells are required for lymph node and Peyer’s patch development in mice. In adult animals, CD4+CD3− cells are found in low numbers in lymphoid organs. Whether adult CD4+CD3− cells are LTi cells and are generated and maintained through cytokine signals has not been directly addressed. In this study we show that adult CD4+CD3− cells adoptively transferred into neonatal CXCR5−/− mice induced the formation of intestinal lymphoid tissues, demonstrating for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
79
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 94 publications
(81 citation statements)
references
References 29 publications
(34 reference statements)
1
79
1
Order By: Relevance
“…These data suggest that IL-7Ra 1 and IL-7Ra À LTi-like cells coexist in the spleen of adult mice and that signals other than IL-7 may be important for the survival of adult LTi-like cells. This idea is in agreement with a most recent finding that in adult spleen the number of adult LTi-like cells between WT and IL-7 À/À mice are equivalent [7].…”
Section: Introductionsupporting
confidence: 82%
See 1 more Smart Citation
“…These data suggest that IL-7Ra 1 and IL-7Ra À LTi-like cells coexist in the spleen of adult mice and that signals other than IL-7 may be important for the survival of adult LTi-like cells. This idea is in agreement with a most recent finding that in adult spleen the number of adult LTi-like cells between WT and IL-7 À/À mice are equivalent [7].…”
Section: Introductionsupporting
confidence: 82%
“…Furthermore adult LTi-like cells, just like their counterparts from embryonic day 15 spleen, restore a significant degree of B/T segregation in the spleen of LTa À/À mice, and up-regulate VCAM-1 and CCL21 protein expression on the stromal cells with which they are associated [6]. Most recently, adult LTi-like cells were shown to induce lymphoid tissue formation in the intestine of CXCR5 À/À mice [7]. Although normal podoplanin (gp38) expression on T-zone stromal cells requires lymphocytes, LTi-like cells can provide lymphotoxin signals required for the expression of podoplanin and CCL21 on T-cell zone stroma, as injection of LTa À/À lymphocytes into RAG-deficient mice up-regulates podoplanin on T-zone stroma, and this is associated with B/T segregation and T-cell organization [8].…”
Section: Introductionmentioning
confidence: 97%
“…Recent data suggest that systemic availability of IL-7 controls the size of the adult Lti pool. 56 We and others have shown that KGF administration restores IL-7 expression, at least in the thymus, in murine models of aging and after BMT. 15,23,26 IL-7 restoration may have contributed to the higher Lti numbers in BM transplant recipients treated with KGF and KGF ϩ PFT-␤.…”
Section: Discussionmentioning
confidence: 99%
“…Like Th17 and fetal LTi cells, innate lymphoid cells have been linked with lymphoid organogenesis. The adoptive transfer of adult CD4 + CD3 − LTi cells into Cxcr5 −/− mice induces the development of intestinal lymphoid tissues 31. Similarly, the increased availability of IL‐7 in transgenic mice has been associated with the LTi cell‐dependent development of additional Peyer's patches, caecal patches and de novo formation of ectopic lymphoid organs 32.…”
Section: Cellular Initiators Of Ectopic Lymphoneogenesismentioning
confidence: 99%